Integrated CMOS relaxation oscillator with the use of accurate current reference, voltage reference, hysteresis comparator, and simple logic block - Ang, Joel Wei Quan (Nanyang Technological University, 2024)
The report below describes the design of a relaxation oscillator that is modelled after the comparator with an internal hysteresis. The circuit also comprises of a voltage reference block, a current steering switch, as well as a logic block to provide feedback to the comparator circuit. The circuit is simulated in the GlobalFoundries 55 nanometre process technology using the Cadence Virtuoso software. The results of the circuit are as follows: temperature coefficient of the voltage reference block is on average 11 ppm per degree Celsius. The oscillator current is able to maintain a stable oscillation with a frequency of approximately 100 Megahertz, or a period that is about 10 nanoseconds.